2020
DOI: 10.1186/s13104-020-04960-3
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between dental caries experience and the level of Streptococcus mutans and lactobacilli in saliva and carious teeth in a Yemeni adult population

Abstract: Objective: This study aimed to determine the relative amounts of Streptococcus mutans (SM) and lactobacilli (LBs) and their relationship with dental caries among a Yemeni adult population. Results: A positive correlation appeared between SM and LB counts from saliva and caries tissue samples and the decayed, missing and filled teeth (DMFT) score (p < 0.05). There was a significant correlation between SM and LBs in caries tissue (p < 0.05). However, there was no significant difference between SM and LBs isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 24 publications
0
17
0
1
Order By: Relevance
“…The Gram-positive bacterium Streptococcus mutans plays a crucial role in dental caries onset and progression [ 7 ], especially due to its capacity to produce organic acids and to withstand stressful conditions such as low pH. It also has the ability to synthesize large amounts of extracellular polymers from sucrose metabolization, thereby promoting supportive conditions for the adhesion and aggregation of other acidogenic and aciduric microorganisms to the biofilm [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Gram-positive bacterium Streptococcus mutans plays a crucial role in dental caries onset and progression [ 7 ], especially due to its capacity to produce organic acids and to withstand stressful conditions such as low pH. It also has the ability to synthesize large amounts of extracellular polymers from sucrose metabolization, thereby promoting supportive conditions for the adhesion and aggregation of other acidogenic and aciduric microorganisms to the biofilm [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, the detection of S. mutans in saliva sample was 100%. In the previous study, S. mutans was present in all of the patients with dental caries (Sounah and Madfa, 2020). S. mutans was present in all saliva samples and that there was a statistically significant link between the number of S. mutans and the DMFT score (Kishi et al, 2009).…”
Section: S Mutans Count P-value Median (Iqr)mentioning
confidence: 82%
“…The bacteriological etiology of tooth decay is commonly due to the presence of S. mutans and lactobacilli microorganisms in dental plaque (1) . It was reported that S. mutans has the responsibility to initiate the carious lesion, while lactobacilli were only responsible for the caries progression (5) . The substance which can act against cariogenic bacteria such as S. mutans and lactobacilli can potentially decrease the incidence of tooth caries (6) .…”
Section: Introductionmentioning
confidence: 99%